Cloud’s Software- Security as a Service(S-SaaS) via Biometrics - Shukla, Surabhi; Kumar, Dharamjeet (International Journal of Computer Sciences and Engineering, 2014)
Cloud computing is considered to be the next generation of information technology framework. It is the next generation computing platforms that can provide dynamic resource pools, virtualization and high availability. The new character brings a lot of new security challenges which have not been taken into account completely in the current cloud computing system. As a consequence, to build a cloud computing data security system is the basis to build cloud computing security system. In this article, the cloud computing technology architecture and the cloud computing data security challenges are the first to be studied and considered, and then the Biometric is raised. At last, the problem definition & resolving strategy has been researched. First of all, user authentication is required to ensure that user data cannot be tampered. Users who pass the authentication can get relative operation on the user data, such as addition, modification, deletion. If the unauthorized user use illegal means to deceive the biometric authentication system, the file entered the system encrypt and privacy defense levels. If key has been got by the intruder. The user data cannot be got valid information even it is obtained through function of privacy protection. It is very important for commercial users of the cloud computing to protect their business secrets.